Emotional Management and Multi-Dimensional Resilience: A Psychosocial Intervention Framework for Flood Victims in Kelantan, Malaysia - Razak, Ateerah Abdul; Hussin, Huzili; Zal, W.A. Amir; Jamalludin, Nur Hafifah; Rusdi, Fairuz Adilah (Universitas Muhammadiyah Surakarta, 2025)
Recurrent severe floods in Kelantan, Malaysia, pose significant and lasting challenges to the psychological and emotional well-being of affected communities. Addressing this critical need, this study focuses on developing an evidence-based psychosocial intervention framework and preparedness guidelines, specifically designed to enhance emotional management and multi-dimensional resilience among flood victims. The research employs a qualitative design, utilizing semi-structured interviews and focus group discussions with flood victims from diverse districts in Kelantan, selected through purposive and snowball sampling to capture rich, contextualized data. The primary objective of this research is to construct actionable preparedness guidelines rooted in emotional and resilience cultivation for future flood events. To achieve this, the study thoroughly examines the emotional resilience of flood-affected communities, elaborates on the diverse forms of community resilience demonstrated, and identifies and analyzes existing emotional management strategies and resilience mechanisms within a comprehensive multi-dimensional framework encompassing psychosocial, spiritual, and behavioral dimensions. The findings show that adaptive strategies are employed by victims, highlighting a crucial interplay between individual emotional fortitude and collective community resilience. This research culminates in a practical, culturally sensitive intervention framework aimed at enhancing the psychological well-being and preparedness of flood victims. By contributing significantly to disaster mental health and community resilience building, this study underscores the importance of holistic approaches in fostering sustainable recovery and alleviating the long-term psychosocial burden of natural disasters within the